Performance Analysis of Squashed Twin band MIMO Array for Wireless Communication Systems - Md. K. Muinuddin Chisti, T. Vidyavathi,G. Radha Kumari, U.N. Subhadra Devi (International Journal of Advanced Science and Technology, 2020)
Squashed two-band Multiple Input and Multiple Output (MIMO) antennas with high level isolation for various wireless communications are designed. The idea of this present work is to design and implement a tiny MIMO antenna operated in dual band of frequencies to trim down the mutual coupling between the radiating elements and to provide prominent isolation between them. Extreme segregation is achieved by using separation or isolation methods such as Parasitic Element (PE), Extensive Ground Plane (EGP) and two Ground Slots (GS). The proposed aerial arrangement of two monopole elements intended to resonate twin band frequencies of 2.400 GHz and 5.200 GHz covering for 3.G. (2.115-2.185 GHz), Wi-Fi and for Bluetooth device (2.45-2.55 GHz), 4G LTE technologies (2.32-2.41 GHz), German frequency band for WIMAX include (5.25-5.35) and WLAN (5.152-5.725 GHz) using FR4 epoxy as a substrate material. The antenna reveals Envelope Correlation Coefficient (ECC) is fewer of 0.002 and 0.001 over the lesser and superior band. The proposed squashed MIMO construction are simulated in HFSS and investigated through radiation patterns, Scattering-parameters.